2016
DOI: 10.1016/j.trc.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of providing traffic information estimated by a stochastic network equilibrium model with stochastic demand

Abstract: To estimate travel times through road networks, in this study, we assume a stochastic demand and formulate a stochastic network equilibrium model whose travel times, flows, and demands are stochastic. This model enables us to examine network reliability under stochastic circumstances and to evaluate the effect of providing traffic information on travel times. For traffic information, we focus on travel time information and propose methods to evaluate the effect of providing that information. To examine the fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…where the random variable Q are generated from a standard continuous MVN Q and then rounded to the nearest integer. When the number of travelers is sufficiently large, the rounding error is negligible [51]. In this paper demand is approximated by a continuous MVN.…”
Section: Notationsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the random variable Q are generated from a standard continuous MVN Q and then rounded to the nearest integer. When the number of travelers is sufficiently large, the rounding error is negligible [51]. In this paper demand is approximated by a continuous MVN.…”
Section: Notationsmentioning
confidence: 99%
“…All these studies indicate the O-D variation is of great importance to network modeling and behavioral analysis. Statistical traffic assignment models consider various O-D probability distributions such as Poisson distributions [19], MVN [13], multinomial distributions [51]. Nakayama and Watling [54] summarized different formulations and proposed a unified framework for stochastic modeling of traffic flows.…”
Section: Introductionmentioning
confidence: 99%
“…As DUE implies network traffic conditions are precisely known to all travelers and they all make the efforts reaching the optimal routes, many studies challenged the DUE in modeling travelers' behaviors and network conditions in real-world networks [37]. Levinson [26], Ben-Elia et al [3], Nakayama [36] showed the accuracy of traffic information provided to travelers has a significant impact on their route selection and the resulting network conditions. Zhu and Levinson [64], Jan et al [22] conducted empirical studies using GPS data and found that most travelers do not follow shortest paths in the network, and some studies indicate that travelers are likely to follow the shortest distance paths [1,44] or hyperpaths [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the severe competition in the ATIS market, nowadays almost all ATIS service providers (e.g., Goggle Map or Amap) offer the basic route guidance service for free. In this case, they begin to seek for profit by providing the value-added ATIS (VATIS) service based on the evidence that people are willing to pay to the save travel time [1][2][3][4][5]. As an actual example, Amap offers several kinds of valueadded services to travelers, such as taxi service, hotel reservation, and online coupons obtaining, which are bringing Amap a tidy profit.…”
Section: Introductionmentioning
confidence: 99%